التأثير الاجتماعي لجرائم المخدرات ( قراءة معرفية في السياسة الجنائية المعاصرة) - صالح فاطمه محمد عبد (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
Due to the multifaceted nature of drug-related crimes, their impact extends far beyond the criminal dimension, encompassing psychological, social, and moral effects. These crimes represent one of the most serious challenges facing societies today, as their consequences are not limited to the dealer or the user, but rather extend to weaken social bonds and destabilize the family structure. This often leads to family disintegration, behavioral deviation, and a rise in crime rates, ultimately undermining the fabric of society. In this context, the role of criminal policy becomes crucial in addressing drug-related crimes through prevention, treatment, and deterrence. Given the complex nature of drug crimes and their profound impact on the social fabric, there is an urgent need to develop criminal policy in Iraq. This development should aim at adopting a preventive approach that integrates punishment with rehabilitation and awareness, while enhancing cooperation among all state institutions to effectively confront this growing threat.